1998
DOI: 10.1152/ajpgi.1998.274.5.g832
|View full text |Cite
|
Sign up to set email alerts
|

Role of mucosal mast cells in early vascular permeability changes of intestinal DTH reaction in the rat

Abstract: Kraneveld, Aletta D., Thea Muis, Andries S. Koster, and Frans P. Nijkamp. Role of mucosal mast cells in early vascular permeability changes of intestinal DTH reaction in the rat. Am. J. Physiol. 274 (Gastrointest. Liver Physiol. 37): G832-G839, 1998.-Previously, it was shown that depletion and stabilization of the mucosal mast cell around the time of challenge were very effective in reducing delayed-type hypersensitivity (DTH) reactions in the small intestine of the rat. The role of mucosal mast cells in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…This DTH-like reaction is classically known as a non-IgE-mediated reaction. Induction of DTH reactions with DNFB has been shown to lead to successful models for contact dermatitis, nonatopic asthma, and small intestinal inflammation (18,29,30). An acute response occurs within 6 h after challenge and is a result of direct mast cell activation and degranulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This DTH-like reaction is classically known as a non-IgE-mediated reaction. Induction of DTH reactions with DNFB has been shown to lead to successful models for contact dermatitis, nonatopic asthma, and small intestinal inflammation (18,29,30). An acute response occurs within 6 h after challenge and is a result of direct mast cell activation and degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…4. Also the number of CAE-positive mast cells was increased after DNFB sensitization and DNS challenge compared with vehiclesensitized and DNS-challenged mice (mast cell number per colon: vehicle/DNS 16 (6 -22), DNFB/DNS 28 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36); results are expressed as median (range); p Ͻ 0.05, n ϭ 6). TNF-␣ is one of the major cytokines released upon mast cell activation.…”
Section: Dnfb-induced Hypersensitivity Is Associated With Mast Cell Amentioning
confidence: 99%
“…The lymphocyte and the mast cell are two key inflammatory cells in the non-atopic reactions in the mouse airways as well as the skin and the intestine (7,30,31). In skin studies, it has been demonstrated that, upon contact sensitization, B lymphocytes are activated to produce hapten-specific immunoglobulin kappa light chains (IgLC) in spleen and lymph nodes (32).…”
Section: Discussionmentioning
confidence: 99%
“…RMCP I may be involved in cardiovascular remodeling via the degradation of fibronectin (22,23) and by the activation of transforming growth factor-β (24,25). On the other hand, RMCP II may contribute to an increase of vascular permeability (26). Therefore, the upregulated chymases, RMCP I and RMCP II, that are found in SHR vascular tissues may be involved in remodeling vascular structures rather than in regulating blood pressure.…”
Section: Fig 4 Angiotensin I-induced Vasoconstrictions In Isolated mentioning
confidence: 99%